Round Table abstract - Aguiar, Alberto (Cirugía del Uruguay, 1973)
The different presentations have focused on specific points within the great chapter of benign anoretal processes, and we believe that these presentations have been complete and specific. The completion of a final summary is therefore a relatively easy task. We hope that it is not a repetition of what was said in each presentation, and we will try to make a synthesis of some general aspects of the subject and other particular ones, which we understand should be highlighted as fundamental concepts. They are for the most part principles that govern the therapeutic behavior of anorectal processes.